Defense working capital fund pricing policies : insights from the Defense Finance and Accounting Service - Keating, Edward G. (Edward Geoffrey), 1965- (RAND, 1999)
The Defense Finance and Accounting Service (DFAS), created in 1991 through the consolidation of military service-specific accounting and finance operations, provides a variety of services to Department of Defense (DoD) customers, such as payroll, bill payment, and generation of accounting statements. Examining DFAS data on expenditures and workload to explore possibilities for improved operations, the authors argue that current linear pricing of DFAS services is inappropriate. In particular, DFAS expenditures neither increase nor decrease commensurate with workload. DFAS's pricing could be improved by a switch to a nonlinear approach, distributing fixed costs among customers using open-the-door transfer payments and charging only incremental costs to customers on a per work unit basis. Such a pricing reform would require changes to current Defense Working Capital Fund (DWCF) regulations.